5G edge computing technology and application prospects - Hongyuan MA; Ziyu XIAO; Zhonggui BU; Yuan ZHAO (Dianxin kexue)
Edge computing is a method of processing data physically close to where data is generated,and it is one of the key technologies of 5G.The development of network technology and the demand of business applications have jointly promoted the maturity of 5G edge computing.The 5G edge computing technology system was elaborated through the perspective of edge infrastructure,edge computing network and edge platform,and the 5G edge computing application was prospected.